Benefits of Cardiac Rehabilitation After Myocardial Infarction: A Literature Review - Lintang Dyah Ayu Pangukir; Nurhikmawati Nurhikmawati; Purwati Pole Rio; Wisudawan Wisudawan; Akina Maulidhany Tahir (Journal of Community Health Provision, 2026)
Cardiac rehabilitation is an essential component of secondary prevention after myocardial infarction, providing multidimensional benefits beyond pharmacological therapy and coronary revascularization. This literature review aims to examine the clinical, functional, psychological, and preventive benefits of cardiac rehabilitation in patients after myocardial infarction. This study employed a narrative literature review design using secondary data from scientific articles obtained through databases such as PubMed, Google Scholar, ScienceDirect, SpringerLink, Elsevier, and other reputable journal sources. Articles were selected based on their relevance to post myocardial infarction cardiac rehabilitation, including outcomes related to cardiac function, left ventricular ejection fraction, exercise capacity, recurrent cardiovascular events, hospitalization, mortality, quality of life, and rehabilitation delivery models. A total of 15 scientific articles met the inclusion criteria and were analyzed in this review. The findings indicate that cardiac rehabilitation after myocardial infarction improves left ventricular function, exercise capacity, and health related quality of life. It also contributes to reducing major adverse cardiovascular events, recurrent myocardial infarction, rehospitalization, and long-term cardiovascular mortality. Home based cardiac rehabilitation, tele rehabilitation, and mobile health-based rehabilitation were found to have comparable effectiveness to conventional center based rehabilitation, particularly in improving access, adherence, and continuity of care. The review also highlights the importance of early initiation, patient adherence, gender sensitive approaches, and program standardization to optimize rehabilitation outcomes. In conclusion, cardiac rehabilitation should be recognized as an integral and evidence-based strategy in the comprehensive management of post myocardial infarction patients. Its implementation should be expanded through flexible, accessible, and patient centered models to improve long term cardiovascular outcomes.